Disease characteristics and clinical outcomes in patients aged less than 40 with chronic lymphocytic leukemia. (February 2018) - Getta, Bartlomiej M.; Devlin, Sean; Park, Jae H.; Tallman, Martin S.; Berman, Ellin
Highlights: We propose defining very young CLL patients as age ≤40 at diagnosis. The very young had similar CLL prognostic features to older patients. Disease progression and treatment response was similar to older patients. Older patients had more secondary malignancies and shorter survival. Abstract: Outcomes in very young CLL patients (age ≤40) are not well characterized. We compared 71 consecutive patients aged ≤40 with 142 "older" matched patients >40 from our institution and used SEER database as an independent comparison group. Patients in the two age groups were diagnosed at similar Rai stage. At diagnosis, very young patients had a similar rate of adverse cytogenetics, IGHV mutation and ZAP70 expression and had lower beta-2-microglobulin and a lower incidence of second malignancies. There was no difference between the groups with respect to incidence of autoimmune manifestations, family history of lymphoma, time to initiation of CLL therapy, response to therapy, or Richter's transformation. Variables including un-mutated IGHV and elevated LDH were associated with shorter times to treatment initiation in both groups. A trend to longer 5-year survival for very young patients in our institution (93% v 82%, p = 0.082) was validated by SEER data.